Remarks on Echinodermata from the South Central Mediterranean Sea based upon collections made during the MARCOS cruise (10 to 20th April, 2007) - MIFSUD, C.; TAVIANI, M.; STOHR, S. (Mediterranean Marine Science, 2009)
The MARCOS cruise, which took place in the South Central Mediterranean Sea on board the RV ‘Urania’, resulted in the collection of 27 species of Echinodermata from shallow to bathyal depths, many from around Malta (the Fisheries Management Zone). The fauna is represented by common to rare taxa already reported from the Mediterranean with the exception of the amphi-Atlantic ophiuroid Ophiotreta valenciennesi rufescens (Koehler, 1896), recorded from the Mediterranean Basin for the first time. Odontaster mediterraneus (von Marenzeller, 1893) and Luidia sarsi Lutken, 1858 are also first records for the Maltese Islands.